2018
DOI: 10.1039/c7dt04665k
|View full text |Cite
|
Sign up to set email alerts
|

Improved hydrogen storage properties of MgH2by the addition of FeS2micro-spheres

Abstract: The sulfide catalyst is a subject of great interest in developing a MgH2 system as a potential hydrogen storage medium. In this work, FeS2 micro-spheres were successfully prepared by the surfactant-assisted solvothermal method, and later were ball milled with MgH2 to fabricate the MgH2-16.7 wt% FeS2 composite. FeS2 addition could dramatically improve both the hydrogenation and dehydrogenation kinetics, and lower the dehydrogenation temperature of MgH2 as well. The MgH2-16.7 wt% FeS2 composite could absorb 3.71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Summing up, theoretical studies allows us to propose the following schemes of the hydrogen induced phase transformations in magnesium: hcp‐Mg→hcp‐MgH x →fcc‐MgH x →rutile‐MgH 2 or bcc‐Mg→bcc‐MgH x →fcc‐MgH x →rutile‐MgH 2 , if the bcc Mg structure is stabilized. The latter can be realized either in presence of hydride forming elements with bcc structure, such as V, Nb, Fe,, Ti‐V−Cr alloys, FeS 2 or in pure Mg subjected to sever plastic deformation (SPD) ,,,. Violation of the regular arrangement of atoms creates conditions for destabilization of the structure, and as a result, facilitates the progress of metastable phase transition.…”
Section: Theoretical Approach To Destabilization Of Hydrogen‐storage mentioning
confidence: 99%
“…Summing up, theoretical studies allows us to propose the following schemes of the hydrogen induced phase transformations in magnesium: hcp‐Mg→hcp‐MgH x →fcc‐MgH x →rutile‐MgH 2 or bcc‐Mg→bcc‐MgH x →fcc‐MgH x →rutile‐MgH 2 , if the bcc Mg structure is stabilized. The latter can be realized either in presence of hydride forming elements with bcc structure, such as V, Nb, Fe,, Ti‐V−Cr alloys, FeS 2 or in pure Mg subjected to sever plastic deformation (SPD) ,,,. Violation of the regular arrangement of atoms creates conditions for destabilization of the structure, and as a result, facilitates the progress of metastable phase transition.…”
Section: Theoretical Approach To Destabilization Of Hydrogen‐storage mentioning
confidence: 99%
“… Photovoltaics: mesoporous silica (MS)@CuO@FeS 2 , P3HT:PCBM:FeS 2 , FeS 2 /graphene, FeS 2 nanotube arrays on ZnO nanotube arrays Optoelectronics : FeS 2 NCs/graphene Magnetoelectronics: CoS 2 /FeS 2 , FeS 2 /FeSe x Hydrogen production: FeS 2 /anatase TiO 2 & Hydrogen storage: MgH 2 –FeS 2 Lithium ion batteries (LIBs): FeS 2 /CNT, FeS 2 @Carbon fibre, FeS 2 /RGO, FeS 2 /N−G composite, FeS 2 /carbon shells on cobalt nanowires, pitaya‐structured FeS 2 @C Sodium ion batteries (SIBs): FeS 2 nanosheet@Fe 2 O 3, Na/FeS 2 , FeS 2 /rGO−A (reduced graphene oxide aerogel), lychee‐like FeS 2 @FeSe 2 core‐shell microspheres, FeS 2 @C yolk–shell nanoboxes, FeS 2 /CNT Supercapacitors: FeS 2 /graphene, FeS 2 /C Environmental remediation: Au@FeS 2 , FeS 2 QDs/SiO 2 ‐chitosan or polypyrrole Hydrogenation: TiO 2 /FeS 2 , FeS 2 /CNT …”
Section: Introductionmentioning
confidence: 99%
“…This improvement was found to be associated with the in-situ formation of MgS and Mo. Zhang et al [173,176] studied the effect of ironbased sulfides, i.e., Fe3S4 and FeS2, and suggested an almost similar mechanism as found for MoS2 except for the formation of Mg2FeH6 phase in addition to MgS and Fe. This reduced the activation energy down to much lower value, i.e., 68.94 kJ/mol H2, in comparison with MoS2 addition.…”
Section: Hydride Hydride Forming Alloys and Sulfide As Catalystmentioning
confidence: 82%
“…Sulfide materials having transition metal as cation and S as anion have attracted attention as catalysts very recently [172][173][174][175][176]. Jia et al [172] prepared MgH 2 -MoS 2 composite and suggested the reduced activation energy of 87 kJ/mol H 2 for desorption.…”
Section: Hydride Hydride Forming Alloys and Sulfide As Catalystmentioning
confidence: 99%